Determinants of unmet need for family planning among currently married reproductive age women at Dewa Chefa District of Oromia special zone, Amhara region, Ethiopia, 2021; a case-control study - Mohammed Ammie; Mastewal Arefaynie; Bezawit Adane; Kedir Hussein; Mohammedsani Hassan (BMC, 2024)
Abstract Background Unmet need for family planning is a proportion of women among reproductive age group who want to stop or delay childbearing but are not using any method of contraception. One in ten married women face unmet need for family planning world-wide whereas, one in five women in Africa. Thus, by understanding factors associated with unmet need specific to the study area; the study contributes to planning and intervention of programs, gives additional finding for controversies in earlier studies, and also helps as a baseline for other researchers conducting studies on similar topics. Methods A community-based unmatched case-control study was conducted from March 29-April 25, 2021 G.C on 462 currently married reproductive age women (154 cases and 308 controls) in Dewa Chefa District. Currently married reproductive-age women who were fecund, and wanted to limit or delay childbearing but were not using any contraceptive methods were taken as cases and currently married reproductive-age women who were using family planning or did not want to use were taken as controls. A structured and pre-tested questionnaire was used to collect data. Collected data were entered into Epi-data 3.1 and exported to SPSS 23 for analysis. Binary Logistic regression was conducted and variables with p-value < 0.05 were taken as statistically significant. Results A total of 462 women participated in this study, with 100% response rate. The mean age of the respondents was 27.92 years (with SD of ± 6.3) Age of woman 35-49 [AOR = 6.6 (1.1-39)], having poor knowledge on family planning [AOR = 1.9 (1.1-3.1)], using family planning decided by husband [AOR = 3.8 (2.1-6.9)], using family planning decided together [AOR = 2.3 (1.07-5.1)] and have no support and disapproval of husband for family planning use [AOR = 2.1 (1.08-4)] were factors significantly associated with unmet need. Conclusion and recommendations Age of the woman, main decider of family planning use, knowledge about family planning and support and approval of spouse for family planning use were found to have significant association with unmet need for family planning. Thus, family planning providers, District health office, and other concerned bodies should strengthen female empowerment and male involvement in the program with strong couple counseling to reduce unmet need.